PENERAPAN MODEL TREFFINGER DI MASA PANDEMI COVID-19 DALAM RANGKA MELATIH KEMAMPUAN BERFIKIR KREATIF MAHASISWA - ilmadi ilmadi; Elda Herlina; Isnurani Isnurani; Ramzil Huda Zarista (Jurnal Karya Pendidikan Matematika, 2021)
The Treffinger model is a series of learning processes designed to solve mathematical problems by students creatively through 3 (three) stages. The first stage is the Basic tool, the second stage is Practice with Process, and the third stage is Working with real Problems. The purpose of this study was to determine how much influence the Treffinger model has in improving students 'creative thinking skills in learning Calculus 1. The formulation of the problem in this study is whether the Treffinger model can improve students' creative thinking skills in learning Calculus 1 ?. Is the creative thinking ability of students in the aspects of analyzing (C4), evaluating (C5) and creating (C6) who learn using the Treffinger model higher than students who learn with the conventional model in the calculus 1 course? The method used in this research is quasi-experimental research. The design used in this study is a design with unequal groups. The conclusion in this study, in general, is that the application of the Treffinger model is effectively used in order to improve students' creative thinking skills in calculus 1 subject. ) and create (C6) who learn using the Treffinger model higher than the ability of students who learn using conventional models.